Association of INS VNTR variants with type 2 diabetes mellitus in overweight to obese subjects in a Bangladeshi population - Rahman, Mahfizur (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2008